Service-dominant logic in the hotel industry: Pathway to brand awareness and loyalty - Sondari, Tanty; Sari, Nur Zeina Maya; Nuraliati, Ayke (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study aims to analyze the influence of service-dominant logic (SDL) on brand attitude, emotional brand attachment, and brand engagement and the impact of these three variables on brand awareness and brand loyalty among hotel users in Bandung City. A quantitative approach was used in this study with data collection techniques through questionnaires distributed to 230 respondents, namely hotel users in Bandung. The structural equation modeling method based on partial least squares (SEM-PLS) was used to test the relationship between variables in the research model. The results of the study indicate that SDL has a significant positive effect on brand attitude, emotional brand attachment, and brand engagement. in addition, brand attitude, emotional brand attachment, and brand engagement also have a positive effect on brand awareness and brand loyalty. These findings indicate that the SDL approach implemented by hotels can strengthen emotional relationships and consumer engagement with the brand, which ultimately increases customer awareness and loyalty to the hotel brand.